2015
DOI: 10.1080/15582159.2015.1028827
|View full text |Cite
|
Sign up to set email alerts
|

School Sector Differences in Student Achievement in Australian Primary and Secondary Schools: A Longitudinal Analysis

Abstract: This article examines school sector differences in student performance Years 3, 5, and 7 in numeracy, reading, writing, spelling and grammar using data from the Longitudinal Study of Australian Children and the national testing program (NAPLAN). At each of the 3 Year levels, there are sizable school sector differences with students from independent schools exhibiting the substantially higher mean scores than Catholic and government school students. However, school sector differences in Years 3 and 5 largely di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…Educational results vary between and among schools and school systems (Marks, ) and between and among metropolitan and regional areas of Australia (ACARA, ). This article maps and examines the spatial patterns of primary school results in literacy and numeracy in metropolitan and remote Australia in relation to advantaged and disadvantaged suburbs in cities, and in government and non‐government schools in different locales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational results vary between and among schools and school systems (Marks, ) and between and among metropolitan and regional areas of Australia (ACARA, ). This article maps and examines the spatial patterns of primary school results in literacy and numeracy in metropolitan and remote Australia in relation to advantaged and disadvantaged suburbs in cities, and in government and non‐government schools in different locales.…”
Section: Introductionmentioning
confidence: 99%
“…Educational outcomes do differ between government and non‐government sectors at an aggregated level. NAPLAN (Marks, ) and senior secondary outcomes (Gemici et al ., ; Marks ) also differ, with the non‐government sector having a higher proportion of students with higher achievement. However, this dichotomous sectoral focus gives little attention to the spatial contexts for differences between government and non‐government schools, or to differences between schools in different locales within each sector.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the existing literature has been at pains to stress how important prior achievement is to academic performance (see, e.g. Marks, ). We, therefore, re‐ran our mixed‐effects regressions with the addition of a school gain variable (to control for achievement in the Year 7 NAPLAN 2 years previous).…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify ceteris paribus effects, we controlled for factors shown in the literature to affect NAPLAN performance: Indigeneity, school type (secondary, combined secondary and primary, and special schools for disabled students), ICSEA, student–teacher ratio, student–non‐teacher ratio, proportion of female students, proportion of students from a non‐English speaking background, exam participation rate, exam exemption rate, total income per student, and a measure of urbanity. Generally, the literature predicts that non‐indigenous female students from a high ICSEA English speaking background in well‐resourced urban schools outperform their peers in most domains (Drew et al., ; Marks, ; Teese, ). Indeed, these determinants of academic success form the basis of the federal government intervention into education (Gonski, ).…”
Section: Context and Empirical Methodologymentioning
confidence: 99%
“…However, studies using more recent and cross-national data have found no advantage due to private schooling once social and academic selectivity into the schools and the school peer group are accounted for (Dronkers & Avram, 2009;Dronkers & Robert, 2008;Nghiem, Nguyen, Khanam, & Connelly, 2015;Sakellariou, 2017). The picture is not uniform across national contexts and educational stages (Jerrim, Parker, Chmielewski, & Anders, 2016;Marks, 2015). In view of the large private-state resource gap in Britain, it is possible that the private school advantage in Britain might be substantive, even if the differential is low or non-existent in other countries where the resource gap is also low (Ndaji, Little, & Coe, 2016).…”
Section: Introductionmentioning
confidence: 99%